2010
DOI: 10.1073/pnas.1016868108
|View full text |Cite
|
Sign up to set email alerts
|

Microfossils in calculus demonstrate consumption of plants and cooked foods in Neanderthal diets (Shanidar III, Iraq; Spy I and II, Belgium)

Abstract: The nature and causes of the disappearance of Neanderthals and their apparent replacement by modern humans are subjects of considerable debate. Many researchers have proposed biologically or technologically mediated dietary differences between the two groups as one of the fundamental causes of Neanderthal disappearance. Some scenarios have focused on the apparent lack of plant foods in Neanderthal diets. Here we report direct evidence for Neanderthal consumption of a variety of plant foods, in the form of phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
270
1
17

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 441 publications
(303 citation statements)
references
References 46 publications
15
270
1
17
Order By: Relevance
“…Prevalence of these taxa in humans seems to correlate with increased intake of starchy foods (Wu et al, 2011;Schnorr et al, 2014;David et al, 2014). Thus, these results show that the gut microbiome of lowland gorillas during high fruit consumption seasons shares important traits with that of traditional human groups, and that starchy foods and dietary shifts to more digestible carbohydrate sources may have had important impacts in the evolution of modern human microbiomes (Henry et al, 2011;McGrew, 2007).…”
Section: Discussionmentioning
confidence: 67%
“…Prevalence of these taxa in humans seems to correlate with increased intake of starchy foods (Wu et al, 2011;Schnorr et al, 2014;David et al, 2014). Thus, these results show that the gut microbiome of lowland gorillas during high fruit consumption seasons shares important traits with that of traditional human groups, and that starchy foods and dietary shifts to more digestible carbohydrate sources may have had important impacts in the evolution of modern human microbiomes (Henry et al, 2011;McGrew, 2007).…”
Section: Discussionmentioning
confidence: 67%
“…The calculi from Spy have remarkable microremain preservation despite being the northernmost samples (50 28 0 21 00 N, 4 40 0 50 00 E), where hunteregatherer plant use is expected to be low (Kelly, 1995). One-third of the starches in this population were of a single type, which is from a USO of the Nympheae (waterlily) family (Henry et al, 2011, Fig. 1d, e, Fig.…”
Section: Results By Sitementioning
confidence: 87%
“…The large number and diagnostic features of the Triticeae starches enabled us to identify them as deriving from Hordeum spp. (wild relatives of barley), and several showed clear evidence of cooking (Henry et al, 2011). The stone tools from both levels also preserved Triticeae starches, date palm phytoliths, and a variety of other starch types ( Fig.…”
Section: Results By Sitementioning
confidence: 94%
See 1 more Smart Citation
“…Studies of plant microremains preserved in soils (Henry et al, 1996(Henry et al, , 2004Albert et al, 1999Albert et al, , 2000Rosen, 2003) and dental calculus (Henry et al, 2011) from Near Eastern sites suggest that Neanderthals may have consumed a variety of plant foods such as date palms and grains. In cold northern European environments, the study of phytoliths and starch grains in dental calculus from Spy Cave (Belgium) indicated that grass seeds and underground storage organisms were part of Neanderthal diet (Henry et al, 2011).…”
Section: Evidence Of Neanderthal Plant Consumptionmentioning
confidence: 99%